Rapid assessment of drug use and sexual HIV risk patterns among vulnerable drugusing populations in Cape Town, Durban and Pretoria, South Africa - Charles Parry; Petal Petersen; Tara Carney; Sarah Dewing; Richard Needle (Taylor & Francis Group, 2008)
This exploratory study examines the links between drug use and high-risk sexual practices and HIV in vulnerable drug-using populations in South Africa, including commercial sex workers (CSWs), men who have sex with men (MSM), injecting drug users (IDUs) and non-injecting drug users who are not CSWs or MSM (NIDUs). A rapid assessment ethnographic study was undertaken using observation, mapping, key informant interviews and focus groups in known 'hotspots' for drug use and sexual risk in Cape Town, Durban and Pretoria. Key informant (KI) and focus group interviews involved drug users and service providers. Purposeful snowball sampling and street intercepts were used to recruit drug users. Outcome measures included drug-related sexual HIV risk behaviour, and risk behaviour related to injection drug use, as well as issues related to service use. HIV testing of drug-using KIs was conducted using the SmartCheck Rapid HIV-1 Antibody Test. Non-injection drug use (mainly cannabis, methaqualone, crack cocaine and crystal methamphetamine) and injection drug use (mainly heroin) was occurring in these cities. Drug users report selling sex for money to buy drugs, and CSWs used drugs before, during and after sex. Most (70%) of the drug-using KIs offered HIV testing accepted and 28% were positive, with rates highest among CSWs and MSM. IDUs reported engaging in needle sharing and needle disposal practices that put them and others at risk for contracting HIV. There was a widespread lack of awareness about where to access HIV treatment and preventive services, and numerous barriers to accessing appropriate HIV and drug-intervention services were reported. Multiple risk behaviours of vulnerable populations and lack of access to HIV prevention services could accelerate the diffusion of HIV. Targeted interventions could play an important role in limiting the spread of HIV in and through these under-reached and vulnerable populations.